A novel congenital myasthenic syndrome due to decreased acetylcholine receptor ion-channel conductance. - Webster, R; Maxwell, S; Spearman, H; Tai, K; Beckstein, O; Sansom, M; Beeson, D (2012)
Muscle acetylcholine receptor ion channels mediate neurotransmission by depolarizing the postsynaptic membrane at the neuromuscular junction. Inherited disorders of neuromuscular transmission, termed congenital myasthenic syndromes, are commonly caused by mutations in genes encoding the five subunits of the acetylcholine receptor that severely reduce endplate acetylcholine receptor numbers and/or cause kinetic abnormalities of acetylcholine receptor function. We tracked the cause of the myasthenic disorder in a female with onset of first symptoms at birth, who displayed mildly progressive bulbar, respiratory and generalized limb weakness with ptosis and ophthalmoplegia. Direct DNA sequencing revealed heteroallelic mutations in exon 8 of the acetylcholine receptor ε-subunit gene. Two alleles were identified: one with the missense substitution p.εP282R, and the second with a deletion, c.798_800delCTT, which result in the loss of a single amino acid, residue F266, within the M2 transmembrane domain. When these acetylcholine receptor mutations were expressed in HEK 293 cells, the p.εP282R mutation caused severely reduced expression on the cell surface, whereas p.εΔF266 gave robust surface expression. Single-channel analysis for p.εΔF266 acetylcholine receptor channels showed the longest burst duration population was not different from wild-type acetylcholine receptor (4.39 ± 0.6 ms versus 4.68 ± 0.7 ms, n = 5 each) but that the amplitude of channel openings was reduced. Channel amplitudes at different holding potentials showed that single-channel conductance was significantly reduced in p.εΔF266 acetylcholine receptor channels (42.7 ± 1.4 pS, n = 8, compared with 70.9 ± 1.6 pS for wild-type, n = 6). Although a phenylalanine residue at this position within M2 is conserved throughout ligand-gated excitatory cys-loop channel subunits, deletion of equivalent residues in the other subunits of muscle acetylcholine receptor did not have equivalent effects. Modelling the impact of p.εΔF266 revealed only a minor alteration to channel structure. In this study we uncover the novel mechanism of reduced acetylcholine receptor channel conductance as an underlying cause of congenital myasthenic syndrome, with the 'low conductance' phenotype that results from the p.εΔF266 deletion mutation revealed by the coinheritance of the low-expressor mutation p.εP282R.